The effects of price liberalisation on Kenyan peri-urban dairy - Staal, Steven J.; Shapiro, Barry I. (International Livestock Research Institute, 1998)
When severe market shortages of dairy products occurred in Kenya in early 1992, the government decontrolled dairy prices and revoked the monopoly of the Kenya Co-operative Creameries (KCC) on sales of processed milk in urban areas. The general opinion among policy makers in Kenya then was that the price liberalisation would adversely affect the KCC. That the KCC has actually not lost its grip on the market is illustrated in this study of the impact of the 1992 policy reform on smallholder peri-urban dairy producers, using a Policy Analysis Matrix (PAM) approach.